The method of complex biological water treatment in aquaponic recirculation systems - Fedorova Valeria; Shvydchenko Sergey; Dubovik Irina; Shvydchenko Darina (E3S Web of Conferences, 2023)
The article discusses the results of experimental research work on the development of technical solutions aimed at creating an integrated innovative biotechnology for recycled water treatment in recirculating aquaculture systems. Schemes and descriptions of experimental units using the multitrophic approach when creating water treatment systems are given. The system is completed according to the principle of integration into a single multitrophic system of spatially delimited biomodules with various types of hydrobionts, where particular types of organisms serve as a food base for subsequent trophic levels. As a result of trophic chains, phytoplankton and zooplankton are cultivated and used as starter live food when rearing juvenile fish. Natural food base contributes to the production of high-quality viable fish stock, which is essential for commercial fish farming. The use of tiered units can significantly reduce the need for production space. Polyculture cultivation of various species of fish, crustaceans, and mollusks together with hydroponic plants allows to diversify production for obtaining additional profit and reducing the risks. Cultivation of high-value fish species (e.g. sturgeon) or crustaceans (Australian red claw) together with less valuable cyprinids, tilapia or African catfish allows to promote products in different market segments.